ANALISIS DETERMINAN TINGKAT KEMISKINAN PROVINSI KALIMANTAN SELATAN TAHUN 2010-2019 - Arif Maulana; Nugrahayu Suryaningrum (Universitas Lancang Kuning, 2022)
Poverty in Indonesia is barrier factor in economic development. One of the successful indicators in the development is decreased poverty rate. This study aims to analyze the poverty level of South Kalimantan Province in 2010-2019. The data used are poverty rate, unemployment rate, Human Development Index, GRDP per capita at constant prices, total population, General Allocation Fund, and Special Allocation Fund, 2010-2019. The analysis method used is panel data regression analysis. The results of the study show that the human development index and GRDP per capita have a negative effect, that means an increasing human development index and GRDP per capita will reduce the poverty rate. Meanwhile, the unemployment rate and special allocation fund have a positive effect, that means an increasing unemployment rate and special allocation fund will be followed by an increasing poverty rate.